Design and Synthesis of Cage Molecules as High Energy Density Materials for Aerospace Applications. Issue 24 (19th November 2020) - Kotha, Sambasivarao; Cheekatla, Subba Rao; Meshram, Milind
Abstract: This account deals with our work on cage systems that was reported during the past two decades. Here, we summarized various new synthetic routes to diverse cage polycycles by employing Claisen rearrangement, Diels−Alder (DA) reaction, [2+2] photocycloaddition, Grignard addition, Fischer indolization, ring‐closing metathesis (RCM), Van Leusen oxazole synthesis, and rearrangement reaction as key steps. Several heterocyclic cage frameworks (oxacycles and oxazoles), polycyclic bisindoles, cage spirocycles, cage energetic systems, D 3 ‐trishomocubanes, cage propellanes and unusual polycycles were designed starting with inexpensive and easily accessible starting materials. In some occasions, we also prepared biologically important triquinane frameworks starting with readily available cage diones via photo‐thermal olefin metathesis strategy under microwave irradiation conditions. This new protocol avoids specialized equipment such as flash vacuum pyrolysis. Additionally, we have also shown interesting rearrangements in cage frameworks to generate unusual new and cage systems with the aid of the Lewis acids such as BF3 .OEt2 . Moreover, these functionalized cage systems can be considered as a useful candidates in material science, medicinal chemistry, and also in drug in design. Abstract : Catalysis for Cages : In this paper, we described several new synthetic methods to diverse cage polycycles by employing Claisen rearrangement, Diels‐Alder (DA) reaction, [2+2] photocycloaddition, Grignard addition, Fischer indolization, ring‐closing metathesis (RCM), Van Leusen oxazole synthesis, and rearrangement reaction as key steps. These cage frameworks can be considered as a useful candidates for high energy high density materials as well as useful precursors to design of new polymers and aza cage molecules are potential anti‐viral compounds in medicinal chemistry and pharmaceutical applications.